2021
DOI: 10.1111/head.14066
|View full text |Cite
|
Sign up to set email alerts
|

A pain in the ear: Two case reports of nervus intermedius neuralgia and narrative review

Abstract: Objective: Present two cases of nervus intermedius neuralgia (NIN) in which patients described unilateral deep ear pain as their primary complaint and present a summary of NIN cases reported in the literature. Background: The nervus intermedius is a tiny branch of the facial nerve that, with neuralgia, can present as a deep ear pain (NIN). The International Classification of Headache Disorders, 3rd edition, (ICHD-3) criteria for an NIN diagnosis include a unilateral deep ear pain with possible radiation that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Unfortunately, no established standard medical treatment exists for this condition, and most of the available options derive from treatments of other types of neuropathic pain in adults. From a review conducted on 114 cases of nervus intermedius neuralgia, the pharmacological management with carbamazepine was found to be the most common and effective approach (total of 30 cases; 18/30 good responders), followed by gabapentin (10 cases; 7/10 good responders) [ 2 ]. Both anticonvulsant drugs are widely used for the management of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, no established standard medical treatment exists for this condition, and most of the available options derive from treatments of other types of neuropathic pain in adults. From a review conducted on 114 cases of nervus intermedius neuralgia, the pharmacological management with carbamazepine was found to be the most common and effective approach (total of 30 cases; 18/30 good responders), followed by gabapentin (10 cases; 7/10 good responders) [ 2 ]. Both anticonvulsant drugs are widely used for the management of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…In case of the failure of a pharmacological approach, surgical interventions, including sectioning of the nervus intermedius, may be considered. This may be performed in conjunction with microvascular decompression of the nervus intermedius and of the adjunct cranial nerves IX and X [ 2 , 3 , 5 , 8 ]. Although those authors that support a surgical option describe a favorable outcome in 90% of the cases, other reports suggest that patients may develop atypical facial pain after an apparently successful surgical intervention [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reports available in the literature interchangeably use the terms nervus intermedius neuralgia and geniculate neuralgia when referring to pain with neuropathic characteristics, affecting the area innervated by the nervus intermedius. A recent narrative review on nervus intermedius neuralgia reported a total of 102 cases with a mean age of 44.8 years old and a higher prevalence in females [2]. As for the etiology, the authors identified neurovascular conflict (48.0% cases) and infections (10.8%) as the most frequent causes, among other precipitating factors (30.3%).…”
Section: Introductionmentioning
confidence: 99%